Interconnected voidscapes: re-imagining Northcliffs cultural landscape through architectural intervention - Mahomed, Nabeel (University of the Witwatersrand, Johannesburg, 2024)
Voidscape is a term that will be used in the research to describe the interconnected network of social, cultural, and spatial voids within Northcliff, serving as a conceptual framework to analyse the gaps and divisions present in the community’s fabric. This research attempts to identify an urban program that finds significant opportunities for design intervention through a detailed analysis of the neighbourhood, eventually addressing the existing void spaces that potentially promote and ignite positive change in the community. The study will identify strategic avenues for an architectural intervention that are in line with the goals and demands of the community. The urban program will act as a guide for the creation of lively, inclusive public areas that foster a sense of belonging and inclusivity for all residents, regardless of their backgrounds or origins. It encourages a feeling of community and connection among locals through this process
A research report submitted in fulfillment of the requirements for the Master of Architecture, In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Voidscape; Northcli; SDG-11: Sustainable cities and communities